1960
DOI: 10.2172/10103842
|View full text |Cite
|
Sign up to set email alerts
|

Piping changes for increased production at B, D, DR, F, C, and H reactors

Abstract: For I05-C Cond. I is existing condition. All flows are at temperature of 95°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1967
1967
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Using only a 23-mm steel stent prosthesis, and therefore without consequently using the oversizing technique, he first reported acceptable results in patients in 2002. [15][16][17] Valves were implanted through a transfemoral arterial retrograde or a transfemoral venous antegrade transseptal approach. CoreValve, a porcine pericardial valve mounted within a Nitinol stent of 5 cm length, is another device currently under clinical investigation in the aortic position.…”
Section: Discussionmentioning
confidence: 99%
“…Using only a 23-mm steel stent prosthesis, and therefore without consequently using the oversizing technique, he first reported acceptable results in patients in 2002. [15][16][17] Valves were implanted through a transfemoral arterial retrograde or a transfemoral venous antegrade transseptal approach. CoreValve, a porcine pericardial valve mounted within a Nitinol stent of 5 cm length, is another device currently under clinical investigation in the aortic position.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the IgM subunit was bound rather weakly to the antigen. Several reports indicated that the reduced products of IgM retained the ability to bind antigen, although they lost the hemagglutinating [28], phage neutralizing [29] or precipitating activities [30,31]. Onoue et al [lo] reported recently that the number of binding sites of an anti-hapten IgM molecule is 6, based on a molecular weight of 1,000,000, and that upon dissociation o f the molecule into 6 S subunits, there was essentially no change in the number of binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Abundances in the sdO star atmosphere are published only for He (×2.8 solar), C (×0.05), N (×25) and Si (×1.4) (cf. Bauer & Husfeld 1995). The absence of substantial O, Ne and Mg lines indicates that these elements are underabundant (probably ×0.1 − 0.3, similar to other sdO stars).…”
Section: Discussionmentioning
confidence: 87%
“…Subdwarf O stars form a fairly inhomogeneous group, spreading over a large range of temperatures, surface gravity and chemical compositions. Different evolutionary and nuclear histories probably contribute to the group of sdO stars, one of the late stages of stellar evolution that leads to the formation of white dwarfs (Bauer & Husfeld 1995).…”
Section: Introductionmentioning
confidence: 99%